Kualitas Informasi Anatomi Radiograf pada Pemeriksaan Sternum dengan Variasi Penyudutan Arah Sinar - Rizki Saputra; Angga Yosainto Bequet (Poltekkes Kemenkes Semarang, 2023)
Background: The sternum's radiographic examination involves the use of Right Anterior Oblique (RAO) and Lateral projections. However, if a patient cannot undergo RAO projection, Left Posterior Oblique (LPO) projection in the supine position and adjusting the central ray angle are alternatives. On another note, deviations from perpendicular alignment among the central ray, image receptor, and object can lead to distortions in shape, impacting image quality. Hence, a study is conducted to investigate the impact of beam angle variations on the quality of anatomical information in sternum radiographs to identify the optimal angle that yields the highest quality anatomical information in sternum radiographs. Methods: This research was quantitative research employing an experimental methodology. Data collection involved employing a single-body phantom, which underwent three exposures at each of the specified angle variations Results: Based on the results of the Kruskal Wallis test, there were significant differences in the quality of radiographic anatomic information (p value 0.05). The angle with the most optimal quality of radiographic anatomical information was an angle of 25° to the left with a mean rank value of 11.00. Conclusions: There was a significant difference in the quality of radiographic anatomic information (p value 0.05). The angle with the most optimal quality of radiographic anatomic information was the angle with the highest mean rank value, which was an angle of 25° to the left.